2010
DOI: 10.5539/ibr.v3n4p96
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Cross-Cultural Adjustment among Expatriate Assignees in Malaysia

Abstract: This paper investigates the affects of personality traits on expatriate cross-cultural adjustment. Based on sample of 332 expatriates working in Malaysia, personality factor found to be a significant determinant of expatriate cross-cultural adjustment in international assignments. Specifically, the results of this study reveal that expatriates in Malaysia with greater agreeableness personality fared better in their general and interaction adjustment. Those with greater extraversion found to adjust better in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
(65 reference statements)
6
25
0
Order By: Relevance
“…As researchers affirm the success of second language learning is due to cognitive as well as affective, motivational, and personality factors. The results of the research were in some respects consistent with the results of prior studies;[163334] Specifically, intercultural competence scores were significantly different among students with introvert-extrovert personality, that was in line with the mentioned studies. Here, greater general competence in cultural adjustment is associated with higher extroversion tendency.…”
Section: Discussionsupporting
confidence: 90%
“…As researchers affirm the success of second language learning is due to cognitive as well as affective, motivational, and personality factors. The results of the research were in some respects consistent with the results of prior studies;[163334] Specifically, intercultural competence scores were significantly different among students with introvert-extrovert personality, that was in line with the mentioned studies. Here, greater general competence in cultural adjustment is associated with higher extroversion tendency.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the unfamiliarity and loneliness associated with the expatriate assignments can lead to conflicts between the expatriate managers and their spouses. Less neurotic spouses may be better equipped to cope with such situations and resolve such situations more quickly than spouses high on neuroticism (Ramalu, Rose, Uli and Kumar 2010).…”
Section: R Gupta Et Al 3562mentioning
confidence: 99%
“…In another study by Charbonneau [69], transformational leadership was related to performance indirectly, through the mediating effects of intrinsic motivation. In a study by Ramalu et al [70], it was revealed that relationship between job performance and personality was mediated through interaction and work adjustment. Based on the pattern of relationships and the role of self-motivation as a mediator between numerous human resource outcomes, it is strongly believed that the relationship of EI and social competencies towards cultural adjustment is mediated by self-motivation.…”
Section: The Mediating Role Of Self-motivationmentioning
confidence: 99%